A rapid colorimetric lateral flow test strip for detection of live Salmonella Enteritidis using whole phage as a specific binder - Charlermroj, Ratthaphol; Makornwattana, Manlika; Phuengwas, Sudtida; Karoonuthaisiri, Nitsara (Frontiers in Microbiology, 2022)
Specific antibodies are essential components of immunoassay, which can be applied for the detection of pathogens. However, producing an antibody specific to live bacterial pathogens by the classical method of immunizing animals with live pathogens can be impractical. Phage display technology is an effective alternative method to obtain antibodies with the desired specificity against selected antigenic molecules. In this study, we demonstrated the power of a microarray-based technique for obtaining specific phage-derived antibody fragments against Salmonella, an important foodborne pathogen. The selected phage-displayed antibody fragments were subsequently employed to develop a lateral flow test strip assay for the detection of live Salmonella. The test strips showed specificity to Salmonella Enteritidis without cross-reactivity to eight serovars of Salmonella or other bacteria strains. The test strip assay requires 15 min, whereas the conventional biochemical and serological confirmation test requires at least 24 h. The microarray screening technique for specific phage-based binders and the test strip method can be further applied to other foodborne pathogens.